2019
DOI: 10.1002/soej.12370
|View full text |Cite
|
Sign up to set email alerts
|

Does School Lunch Fill the “SNAP Gap” at the End of the Month?

Abstract: This article investigates the relationship between the timing of Supplemental Nutrition Assistance Program (SNAP) benefit payments and participation in school lunch and breakfast using the National Household Food Acquisition and Purchase Survey. An event study approach examines participation over the five‐day window before and after the SNAP payment. We find that school lunch participation decreases by 17–23 percentage points immediately after the SNAP payment among 11–18 year olds while breakfast drops by 19–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 49 publications
(68 reference statements)
0
7
0
Order By: Relevance
“…Beharie, Mercado, and McKay (2017) find that among children who are living in poverty, SNAP participants have lower rates of grade retention. Laurito and Schwartz (2019) find that SNAP households are more likely to participate in school lunch at the end of the SNAP benefit cycle. Aurino, Fledderjohann, and Vellakkal (2019) find that adolescents in food-insecure households that school-sponsored lunch programs can mitigate these effects for elementary-aged and middleschool children, there is less evidence on how food availability affects educational attainment for high-school students (Figlio and Winicki, 2005;Schwartz and Rothbart, 2019;Mangrum, 2019).…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…Beharie, Mercado, and McKay (2017) find that among children who are living in poverty, SNAP participants have lower rates of grade retention. Laurito and Schwartz (2019) find that SNAP households are more likely to participate in school lunch at the end of the SNAP benefit cycle. Aurino, Fledderjohann, and Vellakkal (2019) find that adolescents in food-insecure households that school-sponsored lunch programs can mitigate these effects for elementary-aged and middleschool children, there is less evidence on how food availability affects educational attainment for high-school students (Figlio and Winicki, 2005;Schwartz and Rothbart, 2019;Mangrum, 2019).…”
Section: Introductionmentioning
confidence: 83%
“…For each household, benefits are issued on the same day each month, and no household currently receives SNAP benefits more than once per month. As a result, recent studies have shown that households increase the quantity and quality of food expenditures right after SNAP receipt and subsequently decrease consumption, creating a "calorie crunch" just before their next disbursement (Shapiro, 2005;Kuhn, 2018;Tarasuk, McIntyre, and Li, 2007;Castner and Henke, 2011;Todd, 2015;Laurito and Schwartz, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Laurito and Schwartz () also consider the SNAP cycle. They see whether two other large food assistance programs—the NSLP and the SBP—help smooth consumption at the end of the SNAP benefit month.…”
Section: Articles In the Symposiummentioning
confidence: 99%
“…Recent studies on people who participate in multiple nutrition assistance programs concurrently, including SNAP and the Special Supplemental Nutrition Program for Women, Infants, and Children (WIC), suggest improved food security and diet quality relative to people only participating in a single program. 7 , 8 , 9 Nevertheless, many are not participating in multiple programs when they are eligible, and potential participants report stigma, language barriers, and administrative burdens as roadblocks to participation. 10 , 11…”
Section: Introductionmentioning
confidence: 99%